Caffeine as an Active Molecule in Cosmetic Products for Hair Loss: Its Mechanisms of Action in the Context of Hair Physiology and Pathology - Ewelina Szendzielorz; Radoslaw Spiewak (Molecules)
Caffeine has recently attracted attention as a potential remedy for hair loss. In the present review, we look into the molecule’s possible mechanisms of action and pharmacodynamics. At the molecular level, it appears that the physiological effects of caffeine are mainly due to the molecule’s interaction with adenosine pathways which leads to an increase in cAMP level and the stimulation of metabolic activity in the hair follicle. Moreover, caffeine also acts as an antioxidant and may prevent degenerative processes. While the intact stratum corneum seems virtually impenetrable to caffeine and a range of physical and chemical methods have been proposed to facilitate its penetration, hair follicles seem to be both a main entry route into the skin and target structures for caffeine at the same time. Caffeine readily forms bonds with water and other molecules which may influence its bioavailability and should be taken into account when engineering future hair products. The results of clinical studies published so far seem promising; however, the majority of the studies of caffeine-based hair loss products offer a very low level of evidence due to considerable flaws in study designs. Nevertheless, the metabolic activity of caffeine and its ability to enter and accumulate in the hair follicles combined with the results of available clinical trials seem to indicate that caffeine could indeed prove as an effective and safe option in the management of hair loss.